HTS-PEG: a method for high throughput sequencing of the paired-ends of genomic libraries. - Sisi Zhou (Public Library of Science (PLoS), 2012)
Second generation sequencing has been widely used to sequence whole genomes. Though various paired-end sequencing methods have been developed to construct the long scaffold from contigs derived from shotgun sequencing, the classical paired-end sequencing of the Bacteria Artificial Chromosome (BAC) or fosmid libraries by the Sanger method still plays an important role in genome assembly. However, sequencing libraries with the Sanger method is expensive and time-consuming. Here we report a new strategy to sequence the paired-ends of genomic libraries with parallel pyrosequencing, using a Chinese amphioxus (Branchiostoma belcheri) BAC library as an example. In total, approximately 12,670 non-redundant paired-end sequences were generated. Mapping them to the primary scaffolds of Chinese amphioxus, we obtained 413 ultra-scaffolds from 1,182 primary scaffolds, and the N50 scaffold length was increased approximately 55 kb, which is about a 10% improvement. We provide a universal and cost-effective method for sequencing the ultra-long paired-ends of genomic libraries. This method can be very easily implemented in other second generation sequencing platforms.